Penerapan Metode Guided Note Taking untuk Meningkatkan Keterampilan Menulis Siswa Kelas IV SD Negeri 1002 Sayur Mahincat - Mira Yanti Lubis; Sri Wahyuni; Sutan Botung Hasibuan (Dirosah Islamiyah, 2026)
This study aimed to determine: (1) students’ writing skills before the implementation of the outing class and hypnoteaching methods, and (2) students’ writing skills after the implementation of these methods in Grade IV of SD Negeri 0805 Tanjung Baru. The research employed Classroom Action Research (CAR) consisting of two cycles, namely Cycle I and Cycle II, with stages of planning, implementation, observation, and reflection. Data were collected through observation, documentation, and tests. The participants were 30 fourth-grade students, comprising 12 boys and 18 girls. The findings showed that students’ writing skills improved significantly after the application of the outing class and hypnoteaching methods. In the pre-cycle stage, only 10% of students achieved good performance, while most were categorized as poor. In Cycle I, improvement was observed, although the results had not reached the expected target. In Cycle II, 86.67% of students achieved good and very good categories. Observation results also increased from 58.66% in the pre-cycle to 81.16% in Cycle II. Therefore, the outing class and hypnoteaching methods effectively improved students’ writing skills by providing broader observation experiences and stimulating idea expression both orally and in writing.